2020
DOI: 10.3390/en13133457
|View full text |Cite
|
Sign up to set email alerts
|

MHD Heat Transfer in W-Shaped Inclined Cavity Containing a Porous Medium Saturated with Ag/Al2O3 Hybrid Nanofluid in the Presence of Uniform Heat Generation/Absorption

Abstract: In this paper, a 2D numerical study of natural convection heat transfer in a W-shaped inclined enclosure with a variable aspect ratio was performed. The enclosure contained a porous medium saturated with Ag/Al2O3 hybrid nanofluid in the presence of uniform heat generation or absorption under the effect of a uniform magnetic field. The vertical walls of the enclosure were heated differentially; however, the top and bottom walls were kept insulated. The governing equations were solved with numerical simu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…In the last few years, the study of heat transfer has been done inside cavities of different shapes such as U‐shaped, 31 T‐shaped, 32 C‐shaped, 33 L‐shaped, 34 and incinerator‐shaped, 35 the results obtained by these studies show that convection heat flow is enhanced by using a nanofluid instead of basic fluid, in addition, the results have shown that aspect ratio of cavities presents a principal factor on the convection heat flow. The convection heat flow inside cavities containing porous media saturated with nanofluid under magnetic forces effect has been examined by Massoudi et al, 36 Izadi et al, 37 and Zeeshan et al, 38 they pointed out that convection heat flow rises by increasing the Darcy number. Other studies such as Teamah and El‐Maghlany 39 and Mliki et al 40 has been done to examine the effect of uniform heat generation or absorption on the heat transfer performance inside cavities, they pointed out that presence of uniform heat generation improves convective flow, however, the presence of uniform heat absorption reduces it.…”
Section: Introductionmentioning
confidence: 99%
“…In the last few years, the study of heat transfer has been done inside cavities of different shapes such as U‐shaped, 31 T‐shaped, 32 C‐shaped, 33 L‐shaped, 34 and incinerator‐shaped, 35 the results obtained by these studies show that convection heat flow is enhanced by using a nanofluid instead of basic fluid, in addition, the results have shown that aspect ratio of cavities presents a principal factor on the convection heat flow. The convection heat flow inside cavities containing porous media saturated with nanofluid under magnetic forces effect has been examined by Massoudi et al, 36 Izadi et al, 37 and Zeeshan et al, 38 they pointed out that convection heat flow rises by increasing the Darcy number. Other studies such as Teamah and El‐Maghlany 39 and Mliki et al 40 has been done to examine the effect of uniform heat generation or absorption on the heat transfer performance inside cavities, they pointed out that presence of uniform heat generation improves convective flow, however, the presence of uniform heat absorption reduces it.…”
Section: Introductionmentioning
confidence: 99%
“…The effective heat capacitance and thermal dilation coefficient of nanofluid models (Massoudi et al , 2020a, 2020b) are defined as follows: …”
Section: Numerical Modelmentioning
confidence: 99%
“…The magnetic field poses a significant factor that affects the efficiency of heat transfer in various industrial and engineering domains. Much work has therefore been done to investigate the influence of the magnetic field on heat transfer efficiency in cavities of various shapes such as F-shaped (Yadollahi et al , 2017), T-shaped (Hussein et al , 2016; Selimefendigil and Öztop, 2020a), H-shaped (Li et al , 2019; Rahimi et al , 2018), C-shaped (Makulati et al , 2016; Haq et al , 2018; Mliki et al , 2017), W-shaped (Massoudi et al , 2020a), L-shaped (Zhang et al , 2020; Ahmed et al , 2020), U-shaped (Selimefendigil and Öztop, 2020b; Ali et al , 2020), containing saturated porous media nanofluids. The results obtained from these works have shown that convective flow inside cavities increases by increasing the aspect ratio of Darcy number and cavity and decreases with the impact of Lorentz forces induced by magnetic field application.…”
Section: Introductionmentioning
confidence: 99%
“…The nanofluid passing through the microchannel to cool the heat sink being varied such as: air, 35 nitrogen air-gas, 36 a permeable membrane. 37 Due to their highly efficient conductivity, the use of nanofluids to control heat transfer and/or cooling system in various applications is considered among the effective solutions for several researchers such as: Massaoudi et al, [38][39][40][41] Ben hamida et al, [42][43][44][45] and Ben Jaballah et al 46,47 Recent work asserts that MWCNT is among the best to use to improve heat transfer. [48][49][50] Therefore, the three-dimensional analysis of the thermal management of cooling electronic devices is a promising area of research.…”
Section: Introductionmentioning
confidence: 99%